SUKHPRASAVA (NORMAL LABOUR) IN ANCIENT LITERATURE: A REVIEW (AYUSHDHARA, 2021)
Ayurveda value lies in the fact that it is not a medical science dealing solely with treatment of disease. Instead, it offers practical guidelines that apply to every facet of daily existence. It also seeks to reconcile health and lifestyle with universal aspects of existence, and to enhance wellbeing. Earliest available evidence and concept of maternal and child care are present in Rigveda, Yajurveda, Atharvaveda, Upnishada and Samhita. Historical review focused on examining research throughout a period of time, often starting with the first time an issue, concept, theory, phenomena emerged in the literature. Details about mechanism and management of labor are described elaborately. To get relieved from difficulties of labor, certain oblations and enchanting of Mantra are advised. Vivid description of Sukhprasava chronologically presented in this article.